2016
DOI: 10.1002/cm.21276
|View full text |Cite
|
Sign up to set email alerts
|

SLK/LOSK kinase regulates cell motility independently of microtubule organization and Golgi polarization

Abstract: Cell motility is an essential complex process that requires actin and microtubule cytoskeleton reorganization and polarization. Such extensive rearrangement is closely related to cell polarization as a whole. The serine/threonine kinase SLK/LOSK is a potential regulator of cell motility, as it phosphorylates a series of cytoskeleton-bound proteins that collectively participate in the remodeling of migratory cell architecture. In this work, we report that SLK/LOSK is an indispensable regulator of cell locomotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…S1, C to E). Comprehensive literature search further revealed that many of these identified pairs have been reported before (data S2), including the antagonistic interaction between Ste20-like serine/threonine protein kinase (SLK) and ROCK via suppressive phosphorylation of RhoA by SLK (19)(20)(21), the synergistic interaction between fibroblast growth factor receptor 1 (FGFR1)/insulin-like growth factor 1 receptor and MAPK via classical receptor signaling cascade (22)(23)(24)(25)(26), and the antagonistic interaction between Rho GTPase Activating Protein 29 (ARHGAP29) and ROCK (27)(28)(29) via regulators of guanosine triphosphatase activities. Identification of these interaction pairs with literature support indicates that our screen has sufficient power to find important and specific shRNA-drug interactions.…”
Section: Two-hit Screen To Elucidate Signaling Interaction In Cell Mi...mentioning
confidence: 84%
“…S1, C to E). Comprehensive literature search further revealed that many of these identified pairs have been reported before (data S2), including the antagonistic interaction between Ste20-like serine/threonine protein kinase (SLK) and ROCK via suppressive phosphorylation of RhoA by SLK (19)(20)(21), the synergistic interaction between fibroblast growth factor receptor 1 (FGFR1)/insulin-like growth factor 1 receptor and MAPK via classical receptor signaling cascade (22)(23)(24)(25)(26), and the antagonistic interaction between Rho GTPase Activating Protein 29 (ARHGAP29) and ROCK (27)(28)(29) via regulators of guanosine triphosphatase activities. Identification of these interaction pairs with literature support indicates that our screen has sufficient power to find important and specific shRNA-drug interactions.…”
Section: Two-hit Screen To Elucidate Signaling Interaction In Cell Mi...mentioning
confidence: 84%
“…Other effects of SLK in cells include dissolution of actin stress fibers and redistribution to the cell periphery, and loss of cell adhesion [1,10]. Several cytoskeletal proteins have been identified as substrates of SLK, including RhoA [11], ezrin [12,13], paxillin [14], and the p150 Glued dynactin subunit [15,16]. By modulating the cytoskeleton, SLK may control cell motility.…”
Section: Introductionmentioning
confidence: 99%
“…This distinction underscores the regulatory mechanisms that specifically influence actin fiber organization without altering overall protein abundance. Moreover, RhoA, known to be upstream of both SLK and ROCK, plays a pivotal role in the regulatory network affecting the cytoskeleton (4,10,18,23). The interplay between these pathways has been extensively documented, often highlighting the close relationship in regulating cytoskeletal rearrangements (10).…”
Section: The Knockdown Of Slk or Ezrin Resulted In An Increase In Con...mentioning
confidence: 99%